Advancement of steam generation process in water tube boiler using Taguchi design of experiments. (October 2021) - Sathish, T.; Mohanavel, V.; Afzal, Asif; Arunkumar, M.; Ravichandran, M.; Khan, Sher Afghan; Rajendran, Parvathy; Asif, Mohammad
Abstract: Steam generation and utilization are needed in many industries and home appliances with, specific requirements. Though there are numerous categories of boilers available for steam generation, this analysis concentrated on the water tube boiler since it produces more steam and offers better safety measures. Taguchi techniques are considered in this entire research work completed through design of experiments (DOE). Orthogonal array L16 is selected to examine the steam generation with four process parameters and four levels. Selected process parameters are namely temperature of feed water (°C), the pressure of feed water (bar), cold water supply (liters), and boiler drum pressure (bar). The response of this study is the as steam generation to since increasing the steam is a target of this investigation. The experimental value of the steam generation is compared with the desired range; most of the response values are within the predicted value. Further, the superheated steam temperature and pressure analysis were also carried out. The maximum steam generation is achieved as 84.31 L; registered in the 15th run of the experiment.